Constructing national identity : the muscular Jew vs the Palestinian underdog - Dorsey, James M. (2015)
Soccer threads itself as a red line through the 20th century history of the Middle East and North Africa as independence populated the region with nation-states. Soccer was important to the leaders struggling for independence as a means to stake claims, develop national identity and fuel anti-colonial sentiment. For its rulers soccer was a tool they could harness to shape their nations in their own mould; for its citizenry it was both a popular form of entertainment and a platform for opposition and resistance. The sport offers a unique arena for social and political differentiation and the projection of transnational, national, ethnic, sectarian, local, generational and gender identities sparking a long list of literature that dates back more than a century. The sport also constitutes a carnivalesque event that lends itself to provocation of and confrontation with authority — local, national or colonial.